2015
DOI: 10.1111/maec.12288
|View full text |Cite
|
Sign up to set email alerts
|

On some hypotheses of diversity of animal life at great depths on the sea floor

Abstract: Multiple hypotheses have emerged to explain the apparent paradox of high diversity of the deep-sea benthos when the environmental conditions are often predicted to inhibit rather than promote diversity. Many fundamental facets of these paradigms remain incompletely understood despite being central to understanding how deep-sea ecosystems, and more generally all ecosystems, function. Here, we examine nine major paradigms of deep-sea diversity that deserve, in our opinion, a fresh research impetus. We purposely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 183 publications
(365 reference statements)
10
105
1
Order By: Relevance
“…This demonstrates that at community level, ellipse area can be associated with other macrofaunal assemblage characteristics. A concurrent decline in niche area and alpha diversity is consistent with the concept that species have finely partitioned niches, and greater total niche area permits higher biodiversity (McClain and Schlacher, 2015). This relationship may also suggest that the influence of disturbance gradients created by hydrothermalism can result in an impoverished community (McClain and Schlacher, 2015;Bell et al, 2016b).…”
Section: Impact Of Hydrothermal Activity On Community Trophodynamicssupporting
confidence: 77%
“…This demonstrates that at community level, ellipse area can be associated with other macrofaunal assemblage characteristics. A concurrent decline in niche area and alpha diversity is consistent with the concept that species have finely partitioned niches, and greater total niche area permits higher biodiversity (McClain and Schlacher, 2015). This relationship may also suggest that the influence of disturbance gradients created by hydrothermalism can result in an impoverished community (McClain and Schlacher, 2015;Bell et al, 2016b).…”
Section: Impact Of Hydrothermal Activity On Community Trophodynamicssupporting
confidence: 77%
“…Until such data become available we caution against over-confidence in our current catalogs of deep-sea biodiversity. Far from being a "known unknown, " we argue (with McClain and Schlacher, 2015) that total deep-sea species richness cannot be currently estimated with confidence.…”
Section: Discussionmentioning
confidence: 84%
“…Since shallow water species richness is relatively well-known, then it is possible to constrain the contribution of deep-sea species to global species richness. This type of comparative reasoning relies on correctly gauging macroecological relationships, but the question of whether total deep-sea species richness is greater or less than that of shallow waters has not been rigorously tested (McClain and Schlacher, 2015). In reviewing available data, Gray (2002) concluded that species density is similar in coastal and deep sediments at large scales, with deep-sea being more species rich at local scales.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in food availability can lead to a progressive decrease in local abundances of benthic and demersal fauna, with a subsequent decline in overall biodiversity (Pusceddu et al, 2013). Benthic communities may experience periodic cycles of disturbance, recolonization and eventual recovery of communities (McClain and Schlacher, 2015). For example, Hess et al (2005) studied benthic foraminifera contained in a time series of samples taken in Capbreton Canyon (Bay of Biscay, NE Atlantic) after a down-slope turbidity flow event.…”
Section: Canyon Effects On Benthic Sessile Fauna and Infaunamentioning
confidence: 99%